Too fast to think : how to reclaim your creativity in a hyper-connected work culture - Lewis, Chris (New York, NY : Kogan Page, 2016)
"Exposing current work environments and practices, Too Fast to Think argues that these two elements are detrimental to and block creativity from flourishing. Employees are too busy, too overloaded with constant information, and too focused on analytical left brain thinking to allow for diffuse thinking, which is usually when creativity can flow uninterrupted and where the best ideas emerge. Author Chris Lewis promotes a model that re-balances left and right brain thinking, takes a holistic approach to the process of thoughts (including emotional thinking and wellbeing), and promotes eight traits that are inherently linked to creation and innovation. Supported by the latest research he teaches how to retrain the brain into allowing creative ideas to emerge, before being shut down by constant interruptions and self-doubts"--
"Our lives are getting faster and faster. We are engulfed in constant distraction from email, social media and our 'always on' work culture. We are too busy, too overloaded with information and too focused on analytical left-brain thinking processes to be creative. Too Fast to Think exposes how our current work practices, media culture and education systems are detrimental to innovation. The speed and noise of modern life is undermining the clarity and quiet that is essential to power individual thought. Our best ideas are often generated when we are free to think diffusely, in an uninterrupted environment, which is why moments of inspiration so often occur in places completely separate to our offices. To reclaim creativity, Too Fast to Think teaches you how to retrain your brain into allowing creative ideas to emerge, before they are shut down by interruption, distraction or the self-doubt of your over-rational brain. This is essential reading for anyone who wants to maximize their creative potential, as well as that of their team. Supported by cutting-edge research from the University of the Arts London and insightful interviews with business leaders, academics, artists, politicians and psychologists, Chris Lewis takes a holistic approach to explain the 8 crucial traits that are inherently linked to creation and innovation"-- publisher's website.
Includes index.
Keywords: Creative ability; Psychology, -- Industrial; Business & economics, -- Workplace culture; Psychology, -- Creative Ability; Psychology, -- Industrial & Organizational Psychology